Navigating the Central Mediterranean in a Time of 'Crisis': Disentangling Migration Governance and Migrant Journeys. (June 2018) - McMahon, Simon; Sigona, Nando
From 2014 to the end of 2016, over 450, 000 people crossed from North Africa towards Italy via the Central Mediterranean route. The number of people recorded as dead or missing in the same stretch of water steadily increased too. Crisis-talk in the region led to renewed efforts by the European Union and its Member States to govern and control migration to and across the Central Mediterranean. Against this backdrop, this article draws upon over 200 interviews with newly arrived boat migrants and 55 stakeholders in Italy to reveal a fundamental disjuncture between the drivers and dynamics of migration and the assumptions underpinning policy development, the saliency of which becomes apparent at three crucial junctions: along migration land routes; at sea; and upon arrival in Europe. In doing so, the article questions current ways of understanding journeys in research and policy, and highlights their consequences for the governance of migration.